2012
DOI: 10.1039/c2gc16430b
|View full text |Cite
|
Sign up to set email alerts
|

Water mediated Heck and Ullmann couplings by supported palladium nanoparticles: importance of surface polarity of the carbon spheres

Abstract: Heterogeneous palladium nanoparticle catalysts that are supported on amphiphilic carbon spheres (Pd@CSP) have been utilized for water-mediated Heck coupling reactions of aryl halides with different alkenes under phosphine free as well as aerobic conditions. Furthermore, a variety of Heck coupling reactions using different bases and solvents, including organic polar and non-polar solvents, have been explored. Aryl bromides are also well activated in Heck coupling reactions in organic polar solvent and as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 71 publications
2
41
0
Order By: Relevance
“…48 At the end of the reaction, the mixture was cooled to room temperature and the catalyst was isolated by magnetic decantation. The recovered catalyst was thoroughly rinsed with ethyl acetate and distilled water, dried at room temperature, and used without any pretreatment for the next runs.…”
Section: General Procedures For Heck Coupling Reactionmentioning
confidence: 99%
“…48 At the end of the reaction, the mixture was cooled to room temperature and the catalyst was isolated by magnetic decantation. The recovered catalyst was thoroughly rinsed with ethyl acetate and distilled water, dried at room temperature, and used without any pretreatment for the next runs.…”
Section: General Procedures For Heck Coupling Reactionmentioning
confidence: 99%
“…In industry, palladium is used extensively as a heterogeneous catalyst, especially for the reduction of automobile emissions, 1 and for carbon-carbon cross-coupling reactions such as Suzuki, [2][3][4][5] Heck, 6,7 and Stille coupling. 8,9 Suzuki cross-coupling reactions are one of the most widely implemented methods used in the formation of carbon-carbon bonds, and are also very efficient under heterogeneous catalysis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it was not necessary to wash the aqueous mixture to remove excess salts or base. 39 This study showed that the in situ formed palladium nanoparticles were recyclable for up to three cycles without significant loss of catalytic activity. A fifth reaction catalysed by the same palladium(0) nanoparticles gave the product in 61% yield.…”
Section: Characterisation Of In Situ-formed Palladium(0) Nanoparticlesmentioning
confidence: 93%